A double-stranded RNA unwinding activity introduces structural alterations by means of adenosine to inosine conversions in mammalian cells and Xenopus eggs. - Wagner, R W (1989)
Amphibian eggs and embryos as well as mammalian cells have been reported to contain an activity that unwinds double-stranded RNA. We have now found that adenosine residues have been modified in the RNA products of this unwinding activity. Although the modified RNA remains double-stranded, the modification causes the RNA to be susceptible to single-strand-specific RNase and to migrate as a retarded smear on a native polyacrylamide electrophoresis gel. The modification is specific for double-stranded RNA. At least 40% of the adenosine residues can be modified in vitro in a given random sequence RNA molecule. By using standard two-dimensional TLC and HPLC analyses, the modified base has been identified as inosine. Mismatched base-pairing between inosine and uridine appears to be responsible for the observed characteristics of the unwound RNA. The biological significance of this modifying activity and also of the modified double-stranded RNA is discussed.